2009
DOI: 10.1680/gein.2009.16.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Development of rational seismic design method for geogrid-reinforced soil wall combined with fibre-mixed soil-cement and its applications

Abstract: The combined use of a geogrid-reinforced soil wall with a fibre-mixed soil-cement wall (GRSW-FSC) has recently been developed, and its application has grown rapidly. The results of previous centrifuge shaking-table tests have clearly shown the effectiveness of the GRSW-FSC to achieve a higher seismic stability than conventional reinforced soil walls. The current research investigates the effect of geogrid arrangement and the width of the soil-cement wall in order to develop a new rational design method for GRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Gaspard et al (2003) concluded from the results of unconfined compression tests (UCT) on sandy soil-cement samples with inclusion of 0.1% and 0.2% fibers that the addition of fibers does not increase the strength significantly. Researchers such as Park (2009), Izawa et al (2009) and Consoli et al (2010 also studied the behavior of cemented sandy soil with and without fiber reinforcement, and concluded that inclusion of fibers causes an increase in the strength of samples. Studies on the behavior of reinforced cemented clay soil are limited to the work that has been carried out by Khattak and Alrashidi (2006) and Tang et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gaspard et al (2003) concluded from the results of unconfined compression tests (UCT) on sandy soil-cement samples with inclusion of 0.1% and 0.2% fibers that the addition of fibers does not increase the strength significantly. Researchers such as Park (2009), Izawa et al (2009) and Consoli et al (2010 also studied the behavior of cemented sandy soil with and without fiber reinforcement, and concluded that inclusion of fibers causes an increase in the strength of samples. Studies on the behavior of reinforced cemented clay soil are limited to the work that has been carried out by Khattak and Alrashidi (2006) and Tang et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…These methods were developed to achieve a higher performance, low costs, and ecological advantages. Miyata et al (2003), Lai et al (2006), Rowe and Taechakumthorn (2008), and Izawa et al (2009) reported excellent case histories on the combination technology. For the applied technology to restore the damaged geo-structure due to an earthquake, it is required that (1) the construction is easy and speedy, (2) it has a high seismic performance, and (3) the cost-benefit ratio is relatively high.…”
Section: Recent Development Of Reinforced Soil Wall Technology In Japanmentioning
confidence: 99%
“…These methods were developed to achieve a higher performance, low costs, and ecological advantages. Miyata et al (2003), Lai et al (2006), Rowe and Taechakumthorn (2008), and Izawa et al (2009) reported excellent case histories on the combination technology. (Ochiai 2007) 12 Reinforced Soil Walls During Recent Great Earthquakes in Japan.…”
Section: Recent Development Of Reinforced Soil Wall Technology In Japanmentioning
confidence: 99%